2021
DOI: 10.1111/sms.14011
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of prior self‐control exertion on subsequent sporting skill performance

Abstract: The prior exertion of self‐control has previously been shown to negatively affect physical performance, yet the effects on complex sporting skill performance have not been examined. Therefore, this study examined whether prior self‐control exertion influences performance on a field hockey task, alongside measuring plasma cortisol concentration and attention as potential mechanisms to explain any effects. Following familiarization, 13 male hockey players (20 ± 1 years) participated in a randomized, order‐balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(118 reference statements)
0
1
1
Order By: Relevance
“…The results we obtained differed in some cases from those of other investigators, presumably due to the specific sample of subjects [2,5,7,8,21,43,54,56,57,64]. Student athletes do not represent all young people of a similar age.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The results we obtained differed in some cases from those of other investigators, presumably due to the specific sample of subjects [2,5,7,8,21,43,54,56,57,64]. Student athletes do not represent all young people of a similar age.…”
Section: Discussioncontrasting
confidence: 95%
“…The results of the study revealed that to young athletes, there are links between self-control achievement in sports competitions, motivation, and the weakening of self-control [42]. Harmful prior efforts to strengthen self-control have been identified as this may reduce athletic performance [43].…”
Section: Introductionmentioning
confidence: 99%